2010
DOI: 10.1021/jo100776q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mangiferin, Isomangiferin, and Homomangiferin

Abstract: Mangiferin, isomangiferin, and homomangiferin, the xanthone C-glycosides with a wide spectrum of pharmacological effects, were synthesized concisely, featuring a C-glycosylation of a xanthene derivative with perbenzylglucopyranosyl N-phenyltrifluoroacetimidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…While it is abundantly found in the stem bark of mango trees, it has not however been reported before in any angiospermic tree except in Mangifera indica . Initially isolated as a coloring matter from Mangifera indica later isomangiferin and homomangiferin were also reported from the leaves and twigs of the same plant . It is also isolated from the methanolic extract of leaves of Arrabidaea patellifera (about 0.1%) that grows from Mexico to Argentina.…”
Section: Chemosystematic: Natural Source Of Mangiferinmentioning
confidence: 98%
“…While it is abundantly found in the stem bark of mango trees, it has not however been reported before in any angiospermic tree except in Mangifera indica . Initially isolated as a coloring matter from Mangifera indica later isomangiferin and homomangiferin were also reported from the leaves and twigs of the same plant . It is also isolated from the methanolic extract of leaves of Arrabidaea patellifera (about 0.1%) that grows from Mexico to Argentina.…”
Section: Chemosystematic: Natural Source Of Mangiferinmentioning
confidence: 98%
“…In this view, Yu et al described a concise route to 1 and the isoforms isomangiferin ( 2 ) and homomangiferin ( 3 ) . Taking into consideration that the electron‐withdrawing effect of the carbonyl group at the C‐9 decreases the nucleophilicity of the xanthone nucleus, thus explaining the low yield obtained in the first synthesis, the authors opted to perform the C ‐glucosylation on a xanthene precursor followed by carbonyl introduction at C‐9.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…NMR analysis revealed that H-4 exchanges with deuterium of the solvent molecule easily under acidic conditions, allowing facile electrophilic substitution reactions to take place at C-4 position. Wu and colleagues have synthesized mangiferin, isomangiferin and homomangiferin bringing about C-glycosylation of a xanthene derivative with perbenzylglucopyranosyl Nphenyltrifluoroacetimidate [56].…”
Section: Reactions Of Mangiferinmentioning
confidence: 99%